Analisis Faktor-faktor Kesulitan Membaca Permulaan Siswa Kelas II SD Negeri Poris Pelawad 2 - Nuraini, Erika; Oktrifianty, Erdhita; Fathurrohmah, Yoyoh (Lembaga Yasin AlSys, 2021)
This research is a descriptive qualitative research to examine and analyze the data objectively according to the data found in the field. Then the data collected from the research results are described in the form of words. Informants in this study were grade II teachers and grade II students at SD Negeri Poris Pelawad 2 Tangerang City. Data collection techniques used are observation, interviews, tests, and documentation studies. The results of this study aim to find out what factors are the origin of reading difficulties in grade II students at SD Negeri Poris Pelawad 2 Tangerang City. Based on the results of research that has been done by researchers that there are problems that become factors of early reading difficulties, namely the omission of words or letters, pronunciation of words with the help of the teacher, not paying attention to punctuation, hesitation, stuttering, retreats, and self-correction. Therefore, researchers can draw conclusions from the results of research that has been studied that there are still students who are not fluent in reading the beginning, this is caused by lack of motivation to learn, unavailability of family environmental factors, and unavailability of reading materials.